Adaptive identification and interpretation of pressure transient tests of horizontal wells: challenges and perspectives; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Sergeev V. L. Viktor Leonidovich (Petroleum Geology: Current Exploration and Extraction Methods, 2016)
Title screen